Pollen morphology of Austrocylindropuntia Backeb, Maihueniopsis Speg., Opuntia Mill. and Tephrocactus Lem. (Cactaceae, Opuntioideae) of Argentina - Garralla, Silvina Susana (2007)
The pollen morphology of the Cactaceae (Opuntioideae) of Argentina was studied under optical and scanning electron microscopy. The following species were considered: Austrocylindropuntia shaferi (Britton and Rose) Backeberg, Austrocylindropuntia verschaffeltii (Cels ex F. A. C Weber) Backeberg., Austrocylindropuntia vestita (Salm-Dyck) Backeberg, Maihueniopsis boliviana (Salm-Dyck) R. Kiesling, Maihueniopsis darwinii (Henslow) F. Ritter, Maihueniopsis glomerata (Haworth) R. Kiesling, Maihueniopsis ovata (Pfeiffer) F. Ritter, Maihueniopsis pentlandii (Salm-Dyck) R. Kiesling, Opuntia anacantha Spegazzini, Opuntia arechavaletae Spegazzini, Opuntia aurantiaca Lindley, Opuntia chakensis Spegazzini, Opuntia colubrina A. Castellanos, Opuntia ficus-indica (L.) Miller, Opuntia monacantha Haworth, Opuntia salagria Castellanos, Opuntia quimilo K. Schumann, Opuntia schickendantzii F. A. C. Weber, Opuntia schulzii A. Castellanos and Lelong, Opuntia soehrensii Britton and Rose, Opuntia sulphurea Gillies ex Salm-Dyck, Tunilla corrugata (Salm-Dyck) D. R. Hunt and Iliff, Tephrocactus alexanderi (Britton and Rose) Backeberg, Tephrocactus aoracanthus (Lemaire) Lemaire, Tephrocactus articulatus (Pfeiffer) Backeberg, Tephrocactus geometricus (A. Castellanos) Backeberg, Tephrocactus halophilus (Spegazzini) Backeberg, Tephrocactus weberi (Spegazzini) Backeberg. The species of the studied genera are: spheroidal, apolar, radiosymetric. Amb circular. Pantoaperturate. Tectate perforate, tectate imperforate, spinulose, nanospinulose or reticulate. Morphological characteristics of the pollen grain that allows differentiation of the taxa include the type of exine (tectate/semitectate), shape and number of pores and supratectal elements. Differences among the species are discussed and a species key is presented.